Ideologi Argumen-Argumen Keagamaan Tradisi Lingkaran Hidup dalam Kitab Kuning - Iswahyudi Iswahyudi; Udin Safala (Islamica: Jurnal Studi Keislaman, 2019)
This article will show that the implementation of the Javanese Islamic tradition in the form of the ritual of the life cycle (life circle) is the implementation of the ideology of Shāfi‘ī developed by his followers (aṣḥāb). The ideology was then known as the ideology of aṣḥāb al-shāfi‘īyah. The ritual of life in the form of a birth ritual (metu), marriage (manten) and death (mati) has been mentioned in the classic Islamic book (kitab kuning). Allegations that Javanese Islam as syncretic Islam and the adoption of Hindu and Buddhist traditions are wrong. The ritual of the life circle as shown in this article is emerging from within Islam itself as an embodiment of the interpretation of Islamic doctrine. The researcher gets this conclusion after doing research of various classic Islamic books that explain the ritual of the life circle. To find out the conclusion, the researcher used the ideological criticism of Pierre F. Bourdieu. This article, therefore, rejects the views of outsiders such as Geertz, Beatty and Mulder, who explain that the ritual of Javanese Muslim is an impure doctrine of Islam.